Efektifitas Video Animasi Untuk Menilai Keterbatasan Aktivitas Pasien Osteoarthritis: Systematic Review - Rizky Asta Pramestirini; Heny Ekawati; Suhariyati Suhariyarti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Osteoarthritis (OA) is the most common chronic joint disease worldwide, which is one of the leading causes of disability and impaired daily activities. A new computer-based animation questionnaire was developed designed to assess how a person performs simple daily activities, thus focusing on the quality of execution. This study aims to determine the effectiveness of the animated questionnaire to assess activity limitations in osteoarthritis patients. This study is a systematic review of research articles on the effectiveness of animated questionnaires in assessing activity limitations in osteoarthritis patients, with the criteria of a pilot study, randomized controlled trial (RCT), observational study, cross-sectional and longitudinal and intervention, taken from Pubmed, Science Direct, and Scopus with the PICO framework method. The results of the review showed that the animated questionnaire had a positive effect in assessing activity limitations in osteoarthritis patients. This study describes the effectiveness of the use of animated questionnaires on the assessment of activity limitations in osteoarthritis patients. However, a systematic review is needed that focuses more on RCT research articles and their validity to determine the effectiveness of using animated questionnaires.Keywords: osteoarthritis; animated activity questionnaire; videos ABSTRAK Osteoarthritis (OA) merupakan penyakit sendi kronis yang paling umum di seluruh dunia, yang merupakan salah satu penyebab utama kecacatan dan gangguan aktivitas sehari-hari. Kuesioner animasi berbasis komputer baru dikembangkan yang dirancang untuk menilai bagaimana seseorang melakukan aktivitas sehari-hari yang sederhana, sehingga berfokus pada kualitas eksekusi. Studi ini bertujuan untuk mengetahui efektifitas kuesioner animasi untuk menilai keterbatasan aktivitas pada pasien osteoarthritis. Studi ini merupakan systematic review pada artikel-artikel penelitian mengenai efektifitas kuesioner animasi dalam menilai keterbatasan aktivitas pada pasien osteoarthritis, dengan kriteria pilot study, randomized controlled trial (RCT), observational study, cross-sectional dan longitudinal dan intervensi, yang diambil dari Pubmed, Science Direct, dan Scopus dengan metode PICO framework. Hasil review menunjukkan bahwa kuesioner animasi memberikan efek yang positif dalam penilain keterbatasan aktivitas pada pasien osteroatritis. Penelitian ini menggambarkan efektifitas penggunaan kuesioner animasi terhadap penilaian keterbatasan aktivitas pasien osteoatritis. Namun, dibutuhkan systematic review yang lebih berfokus pada artikel-artikel penelitian RCT dan validitas untuk mengetahui efektifitas penggunaan kuesioner animasi.Kata kunci: osteoarthritis; animated activity questionnaire; video